Respuesta :

Answer:

[tex](f+g)(x)=\sqrt{3x+7}+\sqrt{3x-7}[/tex]

[tex]f(g(x))=x+1[/tex]

[tex]f(x)=x+9 \text{ and } g(x)=\frac{4}{x^2}[/tex]

[tex]f^{-1}(x)=\frax{x+2}{3}[/tex]

Let me know if you have any questions about any of my work.

Step-by-step explanation:

You are given the following:

[tex]f(x)=\sqrt{3x+7} \text{ and } g(x)=\sqrt{3x-7}[/tex]

and asked to find [tex](f+g)(x) \text{ which means } f(x)+g(x)[/tex].

If you add those because we are asked to find f(x)+g(x) you get:

[tex]\sqrt{3x+7}+\sqrt{3x-7}[/tex]

----------------------------------------------------------

You are given the following:

[tex]f(x)=x^2+3 \text{ and } g(x)=\sqrt{x-2}[/tex]

and asked to find [tex]f(g(x))[/tex].

[tex]f(g(x))[/tex]

[tex]f(\sqrt{x-2})[/tex] I replaced g(x) with sqrt(x-2) because that is what it equals.

Now this last thing means to replace old input in x^2+3 with new input sqrt(x-2) giving us:

[tex](\sqrt{x-2})^2+3[/tex]

[tex]x-2+3[/tex]

[tex]x+1[/tex]

------------------------------------------------------------

We are given [tex]y=\frac{4}{x^2}+9[/tex] and asked to find g(x) and f(x) such that y=f(g(x)).

We have choices so let's use the choices:

Choice A:

[tex]f(g(x))[/tex]

[tex]f(\frac{4}{x^2}){/tex]    I replace g(x) with 4/x^2:

[tex]\frac{4}{x^2}+9[/tex]  I replaced the old input x with new input 4/x^2.

This was actually the desired result.

-----------------------------------------------------------

To find the inverse of f(x)=3x-2 or y=3x-2, your objective is to swap x and y and then remake y the subject.

y=3x-2

Swap x and y:

x=3y-2

Now solve for y.

Add 2 on both sides:

x+2=3y

Divide both sides by 3:

(x+2)/3=y

y=(x+2)/3

[tex]f^{-1}(x)=\frax{x+2}{3}[/tex]

ACCESS MORE